Conservation Genetics, Precision Conservation, and De‐extinction. (26th July 2017) - Desalle, Rob; Amato, George
Abstract: It has been estimated that three species on the planet now go extinct every hour and that this rate is orders of magnitude higher than the planet has seen in previous catastrophic extinction events. We clearly are in the midst of a sixth extinction, and this one is different from the previous five. Why? This sixth extinction is caused by the activity of a single species—us. If there is any hope of ameliorating this extinction, it will entirely be up to us, as the current stewards of this planet, to change the course. There are many challenges, though, to marshaling this effort. Two primary ones immediately come to mind. The first is that we simply haven't found the right biological tools to address this crisis. The second is that many humans on this planet don't even admit we have a problem. These are two very different problems. The first is primarily technological. Only recently has some of the more advanced biologically focused technology been available to conservation biology and extinction science. Humans are enthralled by cutting‐edge technology for the most part, and for the public, one of the more exciting possibilities in the realm of conservation biology is that some of the more charismatic species that have gone extinct might be resurrected through next‐generation technologies. While our discussion will articulate some weaknesses with the de‐extinction approach to conservation biology, we suggest that the "sexiness" of the technologies used in de‐extinction may simultaneously provide a definition of the techniques viable in conservation biology and afford a teachable moment.